Embedding Covalency into Metal Catalysts for Efficient Electrochemical Conversion of CO2 - Lim, Hyung-Kyu; Shin, Hyeyoung; Goddard, William A., III; Hwang, Yun Jeong; Min, Byoung Koun; Kim, Hyungjun (AMER CHEMICAL SOC, 2014)
CO2 conversion is an essential technology to develop a sustainable carbon economy for the present and the future. Many studies have focused extensively on the electrochemical conversion of CO2 into various useful chemicals. However, there is not yet a solution of sufficiently high enough efficiency and stability to demonstrate practical applicability. In this work, we use first-principles-based high-throughput screening to propose silver-based catalysts for efficient electrochemical reduction of CO2 to CO while decreasing the overpotential by 0.4-0.5 V. We discovered the covalency-aided electrochemical reaction (CAER) mechanism in which p-block dopants have a major effect on the modulating reaction energetics by imposing partial covalency into the metal catalysts, thereby enhancing their catalytic activity well beyond modulations arising from d-block dopants. In particular, sulfur or arsenic doping can effectively minimize the overpotential with good structural and electrochemical stability. We expect this work to provide useful insights to guide the development of a feasible strategy to overcome the limitations of current technology for electrochemical CO2 conversion.
Keywords: CARBON-DIOXIDE; REDUCTION; ELECTRODES; SURFACES; DESIGN; FUELS; MEDIA